La gobernanza del riesgo en América Latina y la dimensión política de los desastres (Estudios) - Jerez Ramírez, Deysi Ofelmina (2022)
Governance in disaster risk reduction (DRR) is a strategy that has been coined in the field of international cooperation, thereby expanding into the different national agendas of the member states. However, its genesis and dissemination reflect tensions and gaps that question the real effectiveness of this model as a preventive strategy. This article analyzes the origins of risk governance, observing the different meanings attributed to it and problematizing the concept given the conditions of vulnerability posed by the Latin American context. From the perspective of political ecology, we have identified that, within this context, local power relations are one of the blind spots of said proposal, which is closely linked to a lack of general understanding of politics and political matters within the elements that make up the DRR governance agenda. The method used for this study is a documentary research approach.